Method for preparing high-strength silicon carbide-based latent heat storage ceramic from lignite

By combining lignite and flour ash balls in the vacuum environment to respond in the vacuum environment, combined with the interaction of oxidatively in the high -temperature microwave vacuum environment, it solves the problem of unable to create high -strength silicon carbide heat storage ceramics in the existing technology. Efficient and low -cost ceramic preparation has excellent thermal performance and pressure resistance.

CN119330745AInactive Publication Date: 2025-01-21ZHALAI NUOER COAL IND CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411484120.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art cannot produce high-strength silicon carbide-based latent heat storage ceramics without introducing additional aluminum sources.

Method used

By mixed with brown coal with charm and coal ash balls, the SIC/Al2O3 powder is obtained in the vacuum environment, and it interacts with oxidation in a high -temperature microwave vacuum environment to prepare high -strength silicon porous ceramics.

Benefits of technology

In the case of adding alumina for additional alumina, high -intensity, low -cost silicon carbide porous ceramics have been prepared, which has high thermal guidance and latent heat storage capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330745A_ABST
    Figure CN119330745A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-strength silicon carbide-based latent heat storage ceramic from lignite, and belongs to the field of heat storage ceramic. The invention aims to solve the problem that the high-strength silicon carbide-based latent heat storage ceramic cannot be manufactured under the condition that an additional aluminum source is not introduced in the prior art. The preparation method comprises the following steps: 1, preparing SiC / Al2O3 powder from lignite and fly ash; 2, adding a sintering aid and a pore-forming agent; 3, compression molding; 4, baking; 5, reacting and sintering in a high-temperature microwave vacuum environment; and 6, performing vacuum impregnation treatment in molten inorganic salt. The method is used for preparing the high-strength silicon carbide-based latent heat storage ceramic from the lignite.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of heat storage ceramics. Background Art

[0002] Shape-fixed phase change latent heat storage materials are usually composed of phase change media and highly thermally conductive porous packaging materials. Their compressive strength is crucial in practical applications and directly affects the structural stability, durability and heat storage effect of the materials. During use, the material needs to withstand external pressure without deformation or cracking to ensure long-term and effective heat storage and remain intact during assembly and transportation, especially in construction applications. Silicon carbide is often used in packaging materials for molten salt heat storage systems due to its excellent thermal conductivity. In order to further improve the compressive strength of silicon carbide porous ceramics, alumina is usually added. As a reinforcing agent, alumina enhances the microstructure of ceramics, improves the density and mechanical strength of the material, and forms a stable interface with the silicon carbide matrix, inhibits crack propagation, and improves compressive performance. In addition, alumina can also enhance the heat resistance of the material, maintain mechanical stability under high temperature conditions, and thus extend the service life of the material in high-temperature heat storage systems. However, the current preparation process of silicon carbide porous ceramics usually requires the addition of additional aluminum sources, which not only increases the cost of raw materials, but also increases the process cost. Summary of the invention

[0003] The present invention aims to solve the problem that the prior art cannot manufacture high-strength silicon carbide-based latent heat storage ceramics without introducing an additional aluminum source, and provides a method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite.

[0004] A method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite is completed by the following steps:

[0005] 1. Mix the lignite and fly ash by ball milling to obtain a mixed powder, and react the mixed powder for 2h to 3h in a vacuum environment at a temperature of 1500℃ to 1600℃ to obtain SiC / Al2O3 powder;

[0006] 2. Add sintering aid and pore former to SiC / Al2O3 powder, then mix evenly by ball milling to obtain prefabricated ceramic raw powder;

[0007] 3. Pressing the prefabricated ceramic raw powder into a shape to obtain a dense ceramic embryo;

[0008] Fourth, placing the dense ceramic green body in a muffle furnace, and sintering it in an air atmosphere at a temperature of 600°C to 800°C to obtain a porous ceramic green body;

[0009] 5. placing the porous ceramic blank in a vacuum high-temperature microwave sintering furnace, and reacting and sintering in a high-temperature microwave vacuum environment to obtain silicon carbide porous ceramics;

[0010] 6. The silicon carbide porous ceramic is placed in a molten inorganic salt for vacuum impregnation treatment, and then taken out and naturally cooled to obtain a high-strength silicon carbide-based latent heat storage ceramic.

[0011] The beneficial effects of the present invention are:

[0012] 1. The present invention uses SiC / Al2O3 powder prepared from lignite and fly ash as raw materials, starch as a pore-forming agent, and yttrium oxide as a sintering aid to prepare silicon carbide porous ceramics without adding additional alumina. Under a high-temperature microwave vacuum environment, the interaction between yttrium oxide and SiC / Al2O3 powder enables the effective preparation of high-strength silicon carbide porous ceramics.

[0013] 2. In the present invention, when the mass of the pore-forming agent is 40% of the mass of the SiC / Al2O3 powder, the bulk density of the silicon carbide porous ceramic prepared in step 5 can reach 3.88 g / cm 3 The open porosity can reach 73%, the pore size can reach 31 μm, and the thermal conductivity of the silicon carbide-based latent heat storage ceramic prepared in step six is ​​as high as 2.6 W / (m·K), and it has a latent heat storage capacity of 55.31 J / g.

[0014] 3. The present invention has the advantages of simple process and easy process control, and is suitable for large-scale industrial production. By using bulk lignite and fly ash as raw materials, the present method not only significantly reduces production costs, but also realizes the high value-added resource utilization of lignite to the greatest extent, thereby improving the comprehensive utilization capacity of lignite in my country. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The XRD spectrum of SiC / Al2O3 powder prepared in step 1 of Example 1;

[0016] Figure 2 The bulk density and open porosity spectrum of the silicon carbide porous ceramic prepared in step 5 of Examples 1 to 4;

[0017] Figure 3 The pore size distribution spectrum of the silicon carbide porous ceramic prepared in step 5 of Examples 1 to 4;

[0018] Figure 4 The element distribution spectrum of the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 of Example 1;

[0019] Figure 5 The thermal conductivity spectrum of the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 of Examples 1 to 4;

[0020] Figure 6A latent heat storage capacity spectrum of the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 of Examples 1 to 4;

[0021] Figure 7 This is a compressive strength spectrum of the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 of Examples 1 to 4. DETAILED DESCRIPTION

[0022] Specific implementation method 1: This implementation method is a method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite, which is completed by the following steps:

[0023] 1. Mix the lignite and fly ash by ball milling to obtain a mixed powder, and react the mixed powder for 2h to 3h in a vacuum environment at a temperature of 1500℃ to 1600℃ to obtain SiC / Al2O3 powder;

[0024] 2. Add sintering aid and pore former to SiC / Al2O3 powder, then mix evenly by ball milling to obtain prefabricated ceramic raw powder;

[0025] 3. Pressing the prefabricated ceramic raw powder into a shape to obtain a dense ceramic embryo;

[0026] Fourth, placing the dense ceramic green body in a muffle furnace, and sintering it in an air atmosphere at a temperature of 600°C to 800°C to obtain a porous ceramic green body;

[0027] 5. placing the porous ceramic blank in a vacuum high-temperature microwave sintering furnace, and reacting and sintering in a high-temperature microwave vacuum environment to obtain silicon carbide porous ceramics;

[0028] 6. The silicon carbide porous ceramic is placed in a molten inorganic salt for vacuum impregnation treatment, and then taken out and naturally cooled to obtain a high-strength silicon carbide-based latent heat storage ceramic.

[0029] The sintering reaction mechanism in step 5 of this specific implementation method is as follows:

[0030] 2Al2O3+2Y2O3→Y4Al2O9 (reaction temperature 900℃~1000℃);

[0031] Y4Al2O9+Al2O3→4YAlO3 (reaction temperature 1100℃~1250℃);

[0032] 3YAlO3+Al2O3→Y3Al5O 12 (Reaction temperature 1400℃~1600℃).

[0033] The principle of the latent heat storage process in step six of this specific implementation method is as follows:

[0034] Endothermic process: solid inorganic salt → liquid inorganic salt;

[0035] Exothermic process: liquid inorganic salt → solid inorganic salt.

[0036] The beneficial effects of this embodiment are:

[0037] 1. This embodiment uses SiC / Al2O3 powder prepared from lignite and fly ash as raw materials, starch as a pore-forming agent, and yttrium oxide as a sintering aid to prepare silicon carbide porous ceramics without adding additional alumina. Under a high-temperature microwave vacuum environment, the interaction between yttrium oxide and SiC / Al2O3 powder enables the effective preparation of high-strength silicon carbide porous ceramics.

[0038] 2. In this embodiment, when the mass of the pore-forming agent is 40% of the mass of the SiC / Al2O3 powder, the bulk density of the silicon carbide porous ceramic prepared in step 5 can reach 3.88 g / cm 3 The open porosity can reach 73%, the pore size can reach 31 μm, and the thermal conductivity of the silicon carbide-based latent heat storage ceramic prepared in step six is ​​as high as 2.6 W / (m·K), and it has a latent heat storage capacity of 55.31 J / g.

[0039] 3. This embodiment has the advantages of simple process and easy process control, and is suitable for large-scale industrial production. By using bulk lignite and fly ash as raw materials, this method not only significantly reduces production costs, but also maximizes the high value-added resource utilization of lignite, thereby improving the comprehensive utilization capacity of lignite in my country.

[0040] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that the mass ratio of lignite to fly ash in step 1 is 1:(1-2). Other aspects are the same as those of specific implementation method 1.

[0041] Specific embodiment 3: This embodiment is different from specific embodiment 1 or 2 in that the ball milling mixing described in step 1 and step 2 is specifically performed at a rotation speed of 200 r / min to 800 r / min and a ball-to-material ratio of (2 to 6):1 for 6 h to 24 h. Other aspects are the same as specific embodiment 1 or 2.

[0042] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that the sintering aid in step 2 is yttrium oxide powder and the pore-forming agent in step 2 is starch. Other aspects are the same as specific embodiments 1 to 3.

[0043] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the mass of the sintering aid described in step 2 is 2% to 5% of the mass of the SiC / Al2O3 powder; the mass of the pore-forming agent described in step 2 is 10% to 40% of the mass of the SiC / Al2O3 powder. The rest is the same as specific embodiments 1 to 4.

[0044] Specific implementation example 6: This implementation example is different from specific implementation examples 1 to 5 in that the compression molding described in step 3 is performed under a pressure of 20 MPa to 200 MPa. The rest is the same as specific implementation examples 1 to 5.

[0045] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: in step 4, the dense ceramic blank is heated to 600°C to 800°C at a rate of 0.5°C / min to 2°C / min in an air atmosphere, and then sintered for 2h to 4h in an air atmosphere at a temperature of 600°C to 800°C. The rest is the same as specific embodiments 1 to 6.

[0046] Specific embodiment eight: This embodiment is different from specific embodiments one to seven in that the reaction sintering described in step five is specifically carried out according to the following steps: in a vacuum environment with a vacuum degree of 0.1Pa to 1Pa and a microwave power of 2kW to 4kW, the porous ceramic blank is first heated to 450℃ to 550℃ at a rate of 8℃ / min to 10℃ / min, then heated to 950℃ to 1050℃ at a rate of 3℃ / min to 5℃ / min, and finally heated to 1600℃ to 1800℃ at a rate of 2℃ / min to 2.5℃ / min, and kept warm for 2h to 4h in a vacuum environment with a vacuum degree of 0.1Pa to 1Pa, a microwave power of 2kW to 4kW and a temperature of 1600℃ to 1800℃, and finally cooled to room temperature at a cooling rate of 5℃ / min to 10℃ / min. The rest is the same as specific embodiments one to seven.

[0047] The sintering process described in this specific embodiment is carried out in a vacuum environment of 0.1 Pa to 1 Pa, while applying a microwave power of 2 kW to 4 kW to achieve uniform heating and enhance the density of the material.

[0048] Specific embodiment 9: This embodiment differs from specific embodiments 1 to 8 in that: the molten inorganic salt in step 6 is molten solar salt or molten Hitec salt; the mass percentage of the inorganic salt in the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 is 40.13% to 60.58%. Others are the same as specific embodiments 1 to 8.

[0049] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the vacuum impregnation treatment described in step 6 is performed under a vacuum degree of 0.1 Pa to 1 Pa for 0.5 h to 2 h. The rest is the same as specific embodiments 1 to 9.

[0050] The following examples are used to verify the beneficial effects of the present invention:

[0051] Embodiment 1:

[0052] A method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite is completed by the following steps:

[0053] 1. At a rotation speed of 400 r / min and a ball-to-material ratio of 6:1, lignite and fly ash were ball-milled for 10 h to obtain a mixed powder. The mixed powder was reacted for 2 h in a vacuum environment at a temperature of 1550 ° C to obtain SiC / Al2O3 powder;

[0054] The mass ratio of the lignite to the fly ash is 1:2;

[0055] 2. Add sintering aid and pore former to SiC / Al2O3 powder, then ball mill for 10 hours at a rotation speed of 400 r / min and a ball-to-material ratio of 6:1 to obtain prefabricated ceramic raw powder;

[0056] The sintering aid is yttrium oxide powder; the pore-forming agent is starch; the mass of the sintering aid is 5% of the mass of SiC / Al2O3 powder; the mass of the pore-forming agent is 40% of the mass of SiC / Al2O3 powder;

[0057] 3. Under the condition of a pressure of 20 MPa, the prefabricated ceramic raw powder is pressed into shape to obtain a dense ceramic embryo;

[0058] The compact ceramic blank has a length of 50 mm, a width of 30 mm and a thickness of 10 mm;

[0059] Fourth, the dense ceramic blank is placed in a muffle furnace, and the temperature is raised to 600°C at a rate of 0.5°C / min in an air atmosphere, and then sintered for 2 hours in an air atmosphere at a temperature of 600°C to remove the pore-forming agent to obtain a porous ceramic blank;

[0060] 5. placing the porous ceramic blank in a vacuum high-temperature microwave sintering furnace, and reacting and sintering in a high-temperature microwave vacuum environment to obtain silicon carbide porous ceramics;

[0061] The reaction sintering is specifically carried out according to the following steps: in a vacuum environment with a vacuum degree of 0.1 Pa and a microwave power of 3 kW, the temperature is first raised to 500°C at a rate of 8°C / min, then raised to 1000°C at a rate of 3°C / min, and finally raised to 1700°C at a rate of 2°C / min, and in a vacuum environment with a vacuum degree of 0.1 Pa, a microwave power of 3 kW and a temperature of 1700°C, the temperature is kept for 2 hours, and finally the temperature is lowered to room temperature at a rate of 5°C / min;

[0062] 6. Under the condition of vacuum degree of 0.1Pa, the silicon carbide porous ceramic is placed in molten inorganic salt for vacuum impregnation for 2 hours, and then naturally cooled after being taken out to obtain high-strength silicon carbide-based latent heat storage ceramics;

[0063] The molten inorganic salt is molten solar salt; the mass percentage of the inorganic salt in the prepared high-strength silicon carbide-based latent heat storage ceramic is 60.58%.

[0064] The lignite and fly ash described in step one are sourced from Zhalainuoer Coal Industry Co., Ltd.; the components of the lignite are specifically 16wt.%, 12wt.%, ash content, 60wt.%, organic carbon content, and 12wt.% inorganic carbon content; the components of the fly ash are specifically 62wt.%, 30wt.%, 30wt.%, 5wt.%, and 3wt.% of silicon oxide and other alkali metal oxides.

[0065] Embodiment 2: This embodiment is different from Embodiment 1 in that the mass of the pore-forming agent in step 2 is 10% of the mass of the SiC / Al2O3 powder; the mass percentage of the molten inorganic salt in the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 is 40.13%. Others are the same as Embodiment 1.

[0066] Embodiment 3: This embodiment differs from Embodiment 1 in that: the mass of the pore-forming agent described in step 2 is 20% of the mass of the SiC / Al2O3 powder; the mass percentage of the molten inorganic salt in the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 is 45.26%. Others are the same as Embodiment 1.

[0067] Embodiment 4: This embodiment differs from Embodiment 1 in that: the mass of the pore-forming agent described in step 2 is 30% of the mass of the SiC / Al2O3 powder; the mass percentage of the molten inorganic salt in the high-strength silicon carbide-based latent heat storage ceramic prepared in step 6 is 55.75%. Others are the same as Embodiment 1.

[0068] Comparative experiment: The difference between this embodiment and the first one of the first to fourth embodiments is that the SiC / Al2O3 powder prepared in step 1 is pickled in a 3M hydrochloric acid aqueous solution for 2 hours to remove the SiC / Al2O3 powder in the powder, and then dried in a 100°C blast drying oven for 12 hours to obtain SiC powder; in step 2, the SiC / Al2O3 powder is replaced by SiC powder. The rest is the same as the first one of the first to fourth embodiments.

[0069] Figure 1 This is the XRD spectrum of SiC / Al2O3 powder prepared in step 1 of Example 1; it can be seen from the figure that the main components of the powder prepared from lignite and fly ash are silicon carbide and aluminum oxide, which shows that SiC / Al2O3 powder can be successfully prepared by the method in the example.

[0070] Figure 2 The bulk density and porosity of the silicon carbide porous ceramics prepared in step 5 of Examples 1 to 4 are shown in the figure. As can be seen from the figure, the bulk density of the silicon carbide porous ceramics obtained when the starch addition amount is 40% is 3.88 g / cm 3 The open porosity is 73%, indicating that the method in the embodiment is successfully used to prepare silicon carbide porous ceramics with high apparent porosity.

[0071] Figure 3 This is the pore size distribution spectrum of the silicon carbide porous ceramic prepared in step 5 of Examples 1 to 4; as can be seen from the figure, the pore size of the silicon carbide porous ceramic obtained when the starch addition amount is 40% is 31μm, indicating that the silicon carbide porous ceramic with micron-level pore size distribution can be successfully prepared by the method in the embodiment.

[0072] Figure 4 This is the element distribution spectrum of the high-strength silicon carbide-based latent heat storage ceramics prepared in step six of Example 1; as can be seen from the figure, after the silicon carbide porous ceramics obtained when the starch addition amount is 40% are impregnated with molten inorganic salt, sodium, potassium, silicon, nitrogen and carbon elements are evenly distributed in the ceramics, indicating that the silicon carbide porous ceramics with a high molten salt content are successfully prepared by the method in the embodiment.

[0073] Figure 5 This is the thermal conductivity spectrum of the high-strength silicon carbide-based latent heat storage ceramics prepared in step six of Examples 1 to 4; it can be seen from the figure that when the starch addition amount is 40%, the thermal conductivity of the silicon carbide-based latent heat storage ceramics is as high as 2.6W / (m·K), indicating that the silicon carbide-based latent heat storage ceramics prepared by the method in the embodiment have excellent thermal response speed in the actual heat storage and release process.

[0074] Figure 6 This is a latent heat storage capacity spectrum of the high-strength silicon carbide-based latent heat storage ceramics prepared in step six of Examples 1 to 4; as can be seen from the figure, when the starch addition amount is 40%, the silicon carbide-based latent heat storage ceramics have a latent heat storage capacity of 55.31 J / g, indicating that the method in the embodiment has successfully prepared silicon carbide thermal storage ceramics with high latent heat capacity.

[0075] Figure 7 This is a compressive strength spectrum of the high-strength silicon carbide-based latent heat storage ceramics prepared in step six of Examples 1 to 4; it can be seen from the figure that when the starch addition amount is 40%, the compressive strength of the silicon carbide-based latent heat storage ceramics prepared by the method in the embodiment is increased from 146.81 MPa to 190.25 MPa compared with the control group, indicating that the method in the embodiment is adopted without additionally introducing Al2O3, using the sintering reaction between the alumina in the lignite and fly ash and the additionally added yttrium oxide, High-strength silicon carbide-based latent heat storage ceramics can be successfully prepared.

Claims

1. A method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite, characterized in that It is done in the following steps:

1. Mix the lignite and fly ash by ball milling to obtain a mixed powder, and react the mixed powder for 2h to 3h in a vacuum environment at a temperature of 1500℃ to 1600℃ to obtain SiC / Al2O3 powder; 2. Add sintering aid and pore former to SiC / Al2O3 powder, then mix evenly by ball milling to obtain prefabricated ceramic raw powder; 3. Pressing the prefabricated ceramic raw powder into a shape to obtain a dense ceramic embryo; Fourth, placing the dense ceramic green body in a muffle furnace, and sintering it in an air atmosphere at a temperature of 600°C to 800°C to obtain a porous ceramic green body; 5. placing the porous ceramic blank in a vacuum high-temperature microwave sintering furnace, and reacting and sintering in a high-temperature microwave vacuum environment to obtain silicon carbide porous ceramics; 6. The silicon carbide porous ceramic is placed in a molten inorganic salt for vacuum impregnation treatment, and then taken out and naturally cooled to obtain a high-strength silicon carbide-based latent heat storage ceramic.

2. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The mass ratio of lignite to fly ash in step 1 is 1:(1-2).

3. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The ball milling mixing described in step 1 and step 2 is specifically carried out for 6h to 24h at a rotation speed of 200r / min to 800r / min and a ball-to-material ratio of (2 to 6):

1.

4. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The sintering aid described in step 2 is yttrium oxide powder; the pore-forming agent described in step 2 is starch.

5. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The mass of the sintering aid described in step 2 is 2% to 5% of the mass of the SiC / Al2O3 powder; the mass of the pore-forming agent described in step 2 is 10% to 40% of the mass of the SiC / Al2O3 powder.

6. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The compression molding described in step three is specifically performed under a pressure of 20 MPa to 200 MPa.

7. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that In step 4, the dense ceramic green body is heated to 600°C to 800°C at a rate of 0.5°C / min to 2°C / min in an air atmosphere, and then sintered for 2h to 4h in an air atmosphere at a temperature of 600°C to 800°C.

8. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The reaction sintering described in step 5 is specifically carried out according to the following steps: in a vacuum environment with a vacuum degree of 0.1Pa~1Pa and a microwave power of 2kW~4kW, the porous ceramic blank is first heated to 450℃~550℃ at a rate of 8℃ / min~10℃ / min, then heated to 950℃~1050℃ at a rate of 3℃ / min~5℃ / min, and finally heated to 1600℃~1800℃ at a rate of 2℃ / min~2.5℃ / min, and in a vacuum environment with a vacuum degree of 0.1Pa~1Pa, a microwave power of 2kW~4kW and a temperature of 1600℃~1800℃, it is kept warm for 2h~4h, and finally cooled to room temperature at a cooling rate of 5℃ / min~10℃ / min.

9. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The molten inorganic salt described in step six is ​​molten solar salt or molten Hitec salt; the mass percentage of the inorganic salt in the high-strength silicon carbide-based latent heat storage ceramic prepared in step six is ​​40.13% to 60.58%.

10. The method for preparing high-strength silicon carbide-based latent heat storage ceramics using lignite according to claim 1, characterized in that The vacuum impregnation treatment described in step six is ​​specifically performed under the condition of a vacuum degree of 0.1 Pa to 1 Pa for 0.5 h to 2 h.

Citation Information

Patent Citations

  • Preparation method of leak-proof composite heat storage material

    CN113651634A

  • Method for preparing SiC-based porous material from lignite and fumed silica

    CN116903377A

  • Method for preparing SiC-based heat storage material through reaction of lignite and silica sol

    CN117025181A

  • Directional heat-conducting anisotropic porous silicon carbide ceramic skeleton, preparation method thereof and application of directional heat-conducting anisotropic porous silicon carbide ceramic skeleton in directional heat management composite phase change material

    CN118771905A